Growing on digital soil: French farmers’ everyday acquisition of new skills online - Calvignac, Cédric; Potier, Victor; Labarthe, Pierre (Agriculture and human values, 2025)
The extent to which digitalisation constitutes a technological revolution for farmers is a subject of considerable debate among researchers, policymakers, and practitioners. However, little is known about farmers’ everyday use of these technologies. Drawing on interviews conducted with 56 French farm managers, this article investigates their use of digital media and online platforms to refine their professional skills and agricultural practices. It reveals that acquiring new agricultural knowledge today involves both traditional institutional actors and online communities, which are driven by strong value-based principles embedded in diverse agricultural models. Our contribution resides in three critical aspects of the adoption of digital platforms and media. First, it emphasises the (s)elective nature of identifying pertinent digital resources, selected based on shared values and a collective vision of the future of agriculture. Second, it introduces the notion of ‘subveillance’, facilitated by digital platforms. This concept refers to farm managers’ inclination to follow news feeds and discern opportunities, thereby engaging in a form of monitoring that operates independently from institutional actors involved in agricultural vocational training and advice. Lastly, it explores the potential of digital platforms—such as WOOFing, crowdfunding, and crowdsourcing—to gauge interest and anticipate the feasibility of agricultural subprojects, thereby enabling the diversification or strengthening of their professional activities.